(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2023)
The development of tidal energy technologies has progressed to where devices can be deployed, operated, maintained, and recovered with some level of assurance that they will and produce adequate levels of power. Equally important to further the tidal energy industry is the ability to site and gain regulatory permission to deploy and operate these devices. This paper sets out a framework for reaching preliminary siting of tidal devices, drawing from case studies from three locations in the US where research studies have provided information in support of tidal deployments. Through the TEAMER funding opportunity in the US, tidal energy device and project developers were able to engage US Department of Energy national laboratory scientists and engineers to provide technical assistance for investigating potential tidal deployment sites within US waters. The bodies of water of interest had already been determined by the proponents at the start of the project and constraints and opportunities within those bodies of water were examined to optimize siting capabilities for the developers. Using numerical models and field observations, we characterized tidal resources at a scale that will allow for optimization of energy extraction. We examined the natural and human infrastructure constraints for deploying and operating tidal devices and arrays including channel widths, bathymetry, vessel traffic, ferry lanes, and grid interconnects, in order to narrow siting options. We also examined the biological resources in the water bodies of interest, with a focus on populations of endangered marine mammals and fish, and the critical habitats that support them. The biological resources were then related to the applicable regulatory requirements in place in US for federal and state statutes in areas where the tidal applicants wish to deploy. Based on these analyses, preferred deployment locations were delineated and processes for meeting regulatory requirements laid out, including post-installation monitoring plans that will be needed. This initial assessment of logistical, regulatory, and environmental conditions for the deployment of a tidal technology is a first step toward the achievement of regulatory compliance for tidal energy projects. Three locations were considered for tidal energy development in the US. The first one included the area around an archipelago of islands in the northern portion of Washington State, near the US-Canada border, with the intent of installing one or more floating tidal devices to add energy resilience and independence for the single utility that services the isolated islands. The second location was in the coastal waters of Maine where tidal power would be added to the local electrical grid. The third location was in Cook Inlet, Alaska, where the applicant seeks to deploy multiple floating tidal devices to provide renewable energy in place of conventionally generated power for the city of Anchorage.